Immobilization of gold nanoparticles on cell culture surfaces for safe and enhanced gold nanoparticle-mediated laser transfection - Kalies, Stefan (Society of Photo-Optical Instrumentation Engineers, 2014)
In comparison to standard transfection methods, gold nanoparticle-mediated laser transfection has proven to be a versatile alternative. This is based on its minor influence on cell viability and its high efficiency, especially for the delivery of small molecules like small interfering RNA. However, in order to transfer it to routine usage, a safety aspect is of major concern: The avoidance of nanoparticle uptake by the cells is desired. The immobilization of the gold nanoparticles on cell culture surfaces can address this issue. In this study, we achieved this by silanization of the appropriate surfaces and the binding of gold nanoparticles to them. Comparable perforation efficiencies to the previous approaches of gold nanoparticle-mediated laser transfection with free gold nanoparticles are demonstrated. The uptake of the immobilized particles by the cells is unlikely. Consequently, these investigations offer the possibility of bringing gold nanoparticle-mediated laser transfection closer to routine usage.